Assessment of nanohardness, elastic modulus, and nanoleakage of the adhesive interface using the ethanol-wet-bonding technique - Souza, Mauricio Yugo [UNESP] (2020)
This study evaluated the effect of ethanol-wet-bonding technique (EWBT) on dentin adhesive infiltration, by means of nanohardness, elastic modulus and nanoleakage, and its stability after 6-month. Forty bovine incisors presenting standardized smear layer were divided into 2 groups, according to EWBT prior to the universal adhesive system in the self-etch mode (Single Bond Universal – 3 M ESPE). Resin blocks were built onto the treated surface (Filtek Z350xt - 3 M ESPE). Half of specimens (n = 20) were evaluated at baseline and the other (n = 20) after 6-month in water storage. Specimens were sectioned into 2-mm thick slices and the adhesive area (composite resin, hybrid layer, and dentin) was analyzed by nanohardness and elastic modulus. Also, slices from the same tooth were qualitatively analyzed by SEM after nanoleakage by silver nitrate. The data obtained were analyzed using two-way ANOVA, Mann-Whitney, and Tukey's test (α = 5%). For nanohardness and elastic modulus, there was difference for evaluated areas (p < 0.001), once dentin presented higher values when compared to hybrid layer. The EWBT groups presented greater nanohardness values at all evaluated periods (p < 0.001). There was statistical difference for aging (p < 0.001), with greater values for baseline. Resin was not affected by the studied variables (p > 0.05). For nanoleakage, EWBT groups presented higher median values on the 6-month evaluation, indicating greater sealing ability over time. EWBT application led to higher values of nanohardness and higher sealing capacity of the adhesive interface when using multimode self-etch adhesive after 6-month water storage.